Evaluating Educational Practices for Positively Affecting Student Perceptions of a Sales Career. (April 2015) - Cummins, Shannon; Peltier, James W.; Pomirleanu, Nadia; Cross, James; Simon, Rob
Despite demand for new graduates seeking a sales position, student reticence toward pursuing a sales career remains. While all students will not choose a sales career, diminishing the existence of sales-related misconceptions among the student population should establish sales as a viable career path for a larger number of students. We test six educational interventions in large Principle of Marketing classes from three different universities ( n = 1, 355) to help identify educational practices for reducing student reticence toward a career in sales. Our results show that while all six educational approaches raise students' perceptions and interest in a selling career, the utilization of experienced salespeople to present classroom materials and to discuss their sales career was the most effective. Classroom lecture and role-plays by university sales students had the second highest intent to pursue intervention scores. We offer recommendations for how to best present sales material to these large, lecture-based courses.